The Ability of Student’S Problem Solving at Senior High School Grade X based on Problem Based Learning - Suci Septiana; Muslimin Ibrahim (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2021)
Problem based learning that involve student to solve authentic problem need to be applied for understanding its role in training students’ problem solving ability. This research aimed to (1) describe the implementation of problem based learning, (2) describe mastery of student’s problem solving ability who are taught problem based learning and (3) describe student’s responses about problem based learning. This research was a pre-experimental using one-group pretest-posttest design. The research sample which selected using purposive sampling were X IPA 6 of MAN Sidoarjo as a experiment class. Data was collected by observation, test and questionnaire. Data were analyzed based on learning implementation, the mastery level of student’s problem solving ability, and student responses. Results showed that problem based learning carried out very good (in the percentage 97.5%). The student’s mastery level of problem solving ability increased with a percentage of 80% after applying problem based learning. Students was positively response to the problem based learning (in the percentage of 86%). Keywords: Problem based learning, Problem solving ability